Ectopic Pregnancy in Uncommon Implantation Sites: Intramural Pregnancy and Rudimentary Horn Pregnancy - Yi Wang; Fan Yu; Li-Qin Zeng (Hindawi Limited, 2015)
Ectopic pregnancy is commonly located in the fallopian tube. Nevertheless, two unusual types of ectopic pregnancy, intramural pregnancy and rudimentary horn pregnancy, seriously threaten maternal life. The diagnosis and treatment of these unusual implantation sites present a clinical challenge. In this study, we illustrated the two unusual types of ectopic pregnancy and summarized the current data regarding diagnosis and optimal treatment from our experience.